Effects of regional meteorological and air conditions on community-acquired pneumonia - examining the interaction of individual, meteorological, and air characteristics - Brenner, Thomas; Link, Ann-Christine; Reudenbach, Christoph; Pott, Hendrik; Rupp, Jan; Witzenrath, Martin; Rohde, Gernot Gerhard Ulrich; Pletz, Mathias; Bertrams, Wilhelm; Schmeck, Bernd (Working papers in innovation and space, 2022)
Climate change will further increase not only the frequency but also the intensity of extreme weather events. As a result, weather conditions favouring pneumonia occurrence - suddenly warmer weather during cold seasons - can increase due to higher meteorological variability which is also linked with climate change. These meteorological trends are expected to lead to adverse effects on peoples' health (Sohn et al., 2019). Community-acquired pneumonia, in the following simply called pneumonia, is one of the most common causes of death worldwide (Aliberti et al., 2021). At the same time, clear linkages between this disease and both meteorological and air conditions are present (Wang et al., 2021). Consequently, it is crucial to understand the effect of these meteorological and air conditions on pneumonia cases more deeply but also more specifically how these effects interact and depend on the personal characteristics and medical backgrounds of patients. It is well studied that especially extreme weather and air conditions, the latter including air quality and wind conditions, have an impact on the number of people hospitalized for pneumonia (Y. Liu et al., 2014; Onozuka et al., 2009). However, many studies analyse the effects of meteorological and air conditions separately with mortality data as an endpoint while predominantly covering the Asian continent and specifically larger cities (Basu & Samet, 2002; Chung et al., 2009; Ge et al., 2013). Therefore, data on other geographical regions and combinations of rural and metropolitan areas are required. Additionally, little is known about how personal characteristics (age, sex) and health background (smoking history, chronic lung diseases, heart insufficiency, overweight) affect the sensitivity of pneumonia cases regarding meteorological and air conditions. We close this research gap by analysing a prospective multicenter cohort that was treated in an in- or outpatient setting for pneumonia in 22 German hospitals or outpatient clinics. The dataset contains personal and health information for more than 10,000 patients. We match this data with daily regional meteorological and air
Keywords: Graue Literatur